Resource provisioning and dimensioning for solar powered cellular base stations - Chamola, Vinay; Sikdar, Biplab (Globecom (2003), 2014)
The deployment of cellular network infrastructure powered by renewable energy sources is gaining popularity as an avenue to provide coverage in areas without reliable grid power and also as a means to reduce the environmental impact of the telecommunications industry. To facilitate the deployment of such networks, this paper addresses the problem of resource provisioning and dimensioning solar powered base stations in terms of the required battery capacity and photo-voltaic (PV) panel sizing. The paper first develops a framework for evaluating the outage probability associated with a base station at a given location as a function of the battery and panel size, by using the solar energy and traffic profiles as inputs. A model is then proposed to evaluate the optimal battery and PV panel sizing, subject to the desired limit on the worst month outage probability. The proposed framework for dimensioning the base station's energy resource requirements has been evaluated using real solar irradiation data for multiple locations.